The international dissemination of Vitruvianism: Erik Forssman and mann erist architecture as bearer of meaning (Bulletin KNOB, 2015)
During the Renaissance, the printed image was an important medium in the circulation of architectural forms throughout Europe. In this process, these disseminated forms gradually changed into ‘local dialects’. Modern research on these forms evolved from a purely stylistic approach to an increased focus on architects and patrons (actors) and, more recently, on art geography. Over time, less attention has been paid to the actual buildings themselves and their meaning. This article focuses on the mannerist period (1575-1625) and the work of Erik Forssman (1915-2011) in a historiographical context.Forssman has made an important contribution to the understanding of the use and reception of architectural treatises. While his dissertation Säule und Ornament (1956) was predominantly theoretical, in his second book Dorisch, Jonisch, Korintisch (1961) he applied his findings to real buildings, coining the term ‘Vitruvianism’ for the reception of classical forms whereby strict application of the rules was secondary to a predominantly meaningful application of the orders within ‘elongated fringes’ of the classical rules.While the focus of research into Renaissance architecture in the Low Countries shifted to early Renaissance (1500-1575) in the south, and (Dutch) Classicism in the north (1625-1700) as well as to the main actors in the design process, the middle period of Mannerism was more or less neglected, unlike in Germany, where the focus stayed on architecture as a bearer of meaning. In his keynote speech at the opening conference in 1989 of the Weserrenaissance-Museum in Schloss Brake near Lemgo (Germany) Forssman reiterated his ideas.It turned out that almost all adaptations of Renaissance forms could be traced back to the Low Countries and that these adapted forms became an export product, not only through prints and treatises distributed all over Europe, but also through itinerant architects and artisans. Reception of these adapted Renaissance (Northern Mannerist) forms led to local dialects. To better understand this, more attention needs to be directed to the actual realization and the intended meaning of the realized architecture. It turns out that often not just one person can be named as ‘auctor intellectualis’ but that a ‘team’ of actors were involved. With the work of Forssman in mind, this article illustrates such a meaningful adaptation by a team of actors with the town hall of Bolsward (1614-1617).A close-reading of the buildings themselves, paying more attention to architecture as a bearer of meaning and to the interaction between ‘imported forms’ and local adaptation by the recipients, can make a significant contribution to the understanding of the ‘complex jigsaw puzzle of architectural exchanges in early modern Europe’.